An Empirical Evaluation of Technical Drawing Didactic in Virtual Worlds - Murad, Sharefa; Passero, Ignazio; Francese, Rita; Tortora, Genoveffa (International Journal of Online and Biomedical Engineering (iJOE), 2011)
This work proposes a 3D Virtual World environment and a didactic experience for training young students in an environment capable of supporting the engineering practices based on technical drawing. The main difficulty of technical drawing consists in representing a 3D object on a 2D medium. This restriction imposes to human mind to be able to summarize the spatial properties of objects on the paper. The proposed system trains these capabilities by requiring students to build, in the simulated environment, simple objects represented with 2D drawings. In this way, the students are not only pushed to move themselves between different dimensionality spaces, but also they benefit of the 3D spaces for moving and exploring the models they are building. An empirical evaluation, conducted as a controlled experiment, has provided enthusiastic results in terms of user performances and impressions.